2017
DOI: 10.3389/fpsyg.2017.01218
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of Music and Visual-Art Related Pleasure – A Critical Integrative Literature Review

Abstract: The present literature review investigated how pleasure induced by music and visual-art has been conceptually understood in empirical research over the past 20 years. After an initial selection of abstracts from seven databases (keywords: pleasure, reward, enjoyment, and hedonic), twenty music and eleven visual-art papers were systematically compared. The following questions were addressed: (1) What is the role of the keyword in the research question? (2) Is pleasure considered a result of variation in the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 74 publications
2
6
0
Order By: Relevance
“…Musical objects are perhaps perceived more straightforwardly as physical stimulation (basic pleasures, see e.g., Berridge & Kringelbach, 2008), while visual objects are enjoyed more as higher-order pleasures (containing evaluative aspects). This is in line with a recent review that showed that music research has studied pleasure particularly through reward and emotion, while visual research has approached pleasure through cognitive processing and as part of aesthetic appreciation (Tiihonen,et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Musical objects are perhaps perceived more straightforwardly as physical stimulation (basic pleasures, see e.g., Berridge & Kringelbach, 2008), while visual objects are enjoyed more as higher-order pleasures (containing evaluative aspects). This is in line with a recent review that showed that music research has studied pleasure particularly through reward and emotion, while visual research has approached pleasure through cognitive processing and as part of aesthetic appreciation (Tiihonen,et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…Does the emotional–motivational constitution of musical pleasure have a similarity with visual pleasure? Finally, the specificity of this constitution to music was explored through comparison with the visual domain, This part of the study was kept purely exploratory in nature, because there is little prior research comparing the pleasure and reward experiences in musical and visual domains (Tiihonen, Brattico, Maksimainen, Wikgren, & Saarikallio, 2017).…”
Section: Objectivementioning
confidence: 99%
“…To our knowledge only one study, thus far, addressed the question of neural mechanisms for attributing beauty value to music (Ishizu and Zeki 2011). This contrasts with the wide interest for understanding the neural correlates of this common type of judgment in visual cognitive neuroscience (Pearce et al 2016;Tiihonen et al 2017).…”
Section: Musical Beauty and The Medial Orbitofrontal Cortexmentioning
confidence: 99%
“…Novelty seeking is not only one of the fundamental propensities of human beings (Fantz, 1964) but also a critical value that is pursued in art (Martindale, 1990;Hekkert and van Wieringen, 1996). Novelty is essential to understanding aesthetic preferences in the field of empirical aesthetics (Berlyne, 1950(Berlyne, , 1970Menninghaus et al, 2019), along with various perceptual (e.g., complexity, symmetry, golden ratio), emotional (e.g., pleasure, empathy, awe), and cognitive (e.g., knowledge, expertise, context) attributes that influence preference decisions (Imamoglu, 2000;Leder et al, 2004;Chatterjee and Vartanian, 2014;Chassy et al, 2015;Street et al, 2016;Jacobsen and Beudt, 2017;Tiihonen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%